1995
DOI: 10.1210/jc.80.9.2700
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the insulin-like growth factors and their binding proteins by glucocorticoid and growth hormone in nonislet cell tumor hypoglycemia

Abstract: Hypoglycemia in patients with nonislet cell tumors is often secondary to overexpression of tumor insulin-like growth factor (IGF) II. In these patients the formation of serum complexes between IGFs, IGF binding protein-3 (IGFBP-3), and the acid-labile subunit (ALS) is impaired. An 87-yr-old woman with nonislet cell tumor hypoglycemia resulting from a localized fibrous tumor of the pleura was treated for 97 days with graded doses of prednisolone (30, 10, and 5 mg/day) followed by GH (1, 4, 8, 4, and 2 U/day). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…Taken together, these changes cause a shift in the molecular distribution of the IGFs from tissue inaccessible to tissue accessible forms, and this phenomenon was for a long time considered to be the primary cause of hypoglycemia in NICTH patients [280,313]. In accordance with this view, stimulation of ternary complex formation by GH treatment has been used to abolish/diminish hypoglycemia in NICTH patients [316].…”
Section: Elevated Levels Of Free Igf-i and -Ii In Non-islet Cell Tumomentioning
confidence: 96%
See 2 more Smart Citations
“…Taken together, these changes cause a shift in the molecular distribution of the IGFs from tissue inaccessible to tissue accessible forms, and this phenomenon was for a long time considered to be the primary cause of hypoglycemia in NICTH patients [280,313]. In accordance with this view, stimulation of ternary complex formation by GH treatment has been used to abolish/diminish hypoglycemia in NICTH patients [316].…”
Section: Elevated Levels Of Free Igf-i and -Ii In Non-islet Cell Tumomentioning
confidence: 96%
“…In normal subjects up to about 80% of the circulating IGF-pool is bound in high-molecular 150 kDa GH-dependent ternary complexes composed of ALS, IGFBP-3 or -5 and IGF-I or -II in a 1:1:1 molar ratio. The ternary complex is, due to its size, confined to the bloodstream, and ternary complexed IGF is therefore unable to provoke hypoglycemia [223,316]. However, NICTH patients are virtually devoid of GH, most likely explained by an increased IGFmediated feedback inhibition, so that levels of IGF-I, IGFBP-3 and ALS are markedly suppressed.…”
Section: Elevated Levels Of Free Igf-i and -Ii In Non-islet Cell Tumomentioning
confidence: 99%
See 1 more Smart Citation
“…ALS, acid-labile subunit; IGF1, insulin-like growth factor 1; IGFBP3, IGF binding protein 3. Medical treatments include chemotherapy, glucocorticoids (Baxter et al 1995, diazoxide (Mitchell et al 1968), recombinant GH (Drake et al 1998), glucagon (Phillips & Robertson 1993), somatostatin analogues (Perros et al 1996) or combinations thereof. Of these, high-dose glucocorticoids are the most successful reducing both big IGF2 production and tumour size.…”
Section: Pituitary Gland ↓ Gh Secretionmentioning
confidence: 99%
“…Since our patient had multiple hepatic metastases, we selected best supportive care with the administration of glucocorticoid. Baxter et al [11] indicated that glucocorticoid therapies suppress peripheral glucose uptake and activate the IGF system. Moreover, glucocorticoids stimulate gluconeogenesis and might also normalize IGFBP profiles and reduce the serum level of big IGF-II [12].…”
Section: Discussionmentioning
confidence: 99%